The transmission distribution, and disaster reconstruction project = (The World Bank in Vietnam (WB), 2003)
The Transmission, Distribution, and Disaster Reconstruction Project's main development objectives are to: a) strengthen the high voltage transmission network in Vietnam to facilitate the evacuation of power from generating stations to the loan centers; b) rehabilitate and expand distribution systems to meet demand, reduce losses and improve relativity; c) support power sector reform and restructuring; and d) support institutional strengthening and commercialization. The disaster component was added after typhoon Linda with the objective to help normalize economic activity in the typhoon affected areas through the reconstruction of the electricity distribution network in such areas. The project contains two distinct components. The Transmission and Distribution Component will: construct transmission lines and substations; expand certain substations; rehabilitate distribution networks; and provide consulting services and demand side management. The Disaster Reconstruction Component consists of reconstruction of low and medium voltage lines, as well as distribution transformer substations damaged by typhoon Linda.